2020
DOI: 10.1111/pce.13744
|View full text |Cite
|
Sign up to set email alerts
|

ABA‐responsive ABRE‐BINDING FACTOR3 activatesDAM3expression to promote bud dormancy in Asian pear

Abstract: Bud dormancy is indispensable for the survival of perennial plants in cold winters.Abscisic acid (ABA) has essential functions influencing the endo-dormancy status. Dormancy-associated MADS-box/SHORT VEGETATIVE PHASE-like genes function downstream of the ABA signalling pathway to regulate bud dormancy. However, the regulation of DAM/SVP expression remains largely uncharacterized. In this study, we confirmed that endo-dormancy maintenance and PpyDAM3 expression are controlled by the ABA content in pear (Pyrus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
98
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 56 publications
7
98
0
Order By: Relevance
“…It might also suggest that ABA response is saturated in the context of very high ABA levels during endodormancy, therefore limiting the effect of additional ABA. Nevertheless, we observed that dormancy release was triggered in buds treated with fluridone that inhibits ABA biosynthesis, as previously reported in pear (Yang et al 2020), thus suggesting that high ABA levels may act to maintain dormancy. This was further confirmed by the observed elevated ABA levels correlated with endodormancy in both cultivars, as well as the differences in ABA levels between the early and late flowering cultivars.…”
Section: Dormancy Depth Is Correlated With Endogenous Aba Contentsupporting
confidence: 87%
“…It might also suggest that ABA response is saturated in the context of very high ABA levels during endodormancy, therefore limiting the effect of additional ABA. Nevertheless, we observed that dormancy release was triggered in buds treated with fluridone that inhibits ABA biosynthesis, as previously reported in pear (Yang et al 2020), thus suggesting that high ABA levels may act to maintain dormancy. This was further confirmed by the observed elevated ABA levels correlated with endodormancy in both cultivars, as well as the differences in ABA levels between the early and late flowering cultivars.…”
Section: Dormancy Depth Is Correlated With Endogenous Aba Contentsupporting
confidence: 87%
“…Additional work is required to ascertain if the decrease of MdDAM1 gene expression in low-chill apple cultivars is due to this mutation or other effects such as epigenetic gene regulation at the transcriptional level as shown for the DAM6 gene present on the EVG locus ( Leida et al, 2012 ). It is also plausible that hormones such as abscisic acid (ABA) play a role in the regulation of MdDAM1 as shown for Maleae and Prunus DAM genes, namely, PpDAM1/PpDAM3 in Japanese pear ( P. prifolia ) and PmDAM6 in Japanese apricot ( Prunus mume ) ( Tuan et al, 2017 ; Falavigna et al, 2019 ; Yamane et al, 2019 ; Yang et al, 2020 ). ABA-mediated regulation of MADS-box genes orthologs of the SVP clade is also important in the distant tree hybrid aspen to promote growth cessation and bud dormancy ( Singh et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, a feedback regulatory mechanism has been described involving repression of PpDAM1 by an abscisic acid response element (ABRE)-binding transcription factor (PpAREB1) in pear (Tuan et al, 2017). More recently, pear ABRE-BINDING FACTOR3 (PpyABF3) has been reported to specifically bind and activate PpyDAM3 expression, whereas PpyABF2/PpAREB1 represses PpyDAM3 by dimerising with PpyABF3 (Yang et al, 2020). Among DAM regulatory proteins, the most studied ones are C-Repeat Binding Factors (CBF), which are able to bind and activate DAM promoters by yeast one-hybrid and transient expression experiments in Japanese apricot and pear (Saito et al, 2015;Niu et al, 2016;Zhao et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%